Comparative Analysis of Fatty Acid Bioaccessibility in Commercial Marine Oil Supplements: An In Vitro Integrated Analytical Study - Thomas Montebugnoli; Giorgia Antonelli; Elena Babini; Ester Maria Vasini; Francesca Danesi; Sigrún Huld Jónasdóttir; María Gudjónsdóttir; Francesco Capozzi; Alessandra Bordoni (Foods, 2024)
Zooplankton such as copepods and krill are currently used to produce marine oil supplements, with the aim of helping consumers achieve the recommended intake of n-3 long chain polyunsaturated fatty acids (n-3 LC-PUFAs). Oils from lower trophic levels differ from fish oil in the distribution of lipids into different classes, and this can influence the bioaccessibility of fatty acids, i.e., the percentage of fatty acids that are released into the intestine in a form that can be absorbed by enterocytes. We evaluated fatty acid release after in vitro digestion in four commercial marine oil supplements containing fish, krill and Calanus finmarchicus oils using two different analytical approaches, TLC-FID and 1H-NMR spectroscopy. The results clearly indicated that the release of free fatty acids (FFAs) after simulated digestion mainly depends on the oil source and is mainly related to the partitioning of lipids into different classes. In fact, the lowest FFA release was detected in Calanus oils, which contain high amounts of wax esters. The different release of FFAs, which appeared secondarily related to encapsulation, can modulate the absorption and blood concentration of the administered n-3 LC-PUFAs and therefore their efficacy. This may partly explain the inconsistencies in intervention studies using marine oil supplements.